Hepatitis B Virus Reactivation Increased the Risk of Developing Hepatic Failure and Mortality in Cirrhosis With Acute Exacerbation - Zhu, Ying; Li, Hai; Wang, Xianbo; Zheng, Xin; Huang, Yan; Chen, Jinjun; Meng, Zhongji; Gao, Yanhang; Qian, Zhiping; Liu, Feng; Lu, Xiaobo; Shi, Yu; et al. (Frontiers in Microbiology, 2022)
Background & Aims: Hepatitis B virus (HBV) reactivation is a serious condition and has been extensively described in chemotherapeutic immunosuppressive population. However, little is known about HBV reactivation in immunocompetent patients with chronic hepatitis B (CHB). In this study we evaluated the prevalence and the clinical significance of HBV reactivation in CHB patients with acute exacerbations. Method: Patients were screened from 2 prospective multicenter observational cohorts (CATCH-LIFE cohort). A total of 1020 CHB patients with previous antiviral treatment history were included to assess the prevalence, risk factors, clinical characteristics of HBV reactivation, and its influence on the progression of chronic liver disease. Results: The prevalence of HBV reactivation was 51.9% in CHB patients with acute exacerbations who had antiviral treatment history in our study. Among the 529 patients with HBV reactivation, 70.9% of them were triggered by discontinued antiviral treatment and 5.9% by nucleos(t)ide analogs (NUCs) resistance. The prevalence of antiviral treatment disruption and NUCs resistance in patients with HBV reactivation is much higher than that in the patients without (70.9% vs 0.2%, and 5.9% vs 0, respectively, both P<0.001). Stratified and interaction analysis showed that HBV reactivation was correlated with high short-term mortality in cirrhosis subgroup (HR = 2.1, P<0.001). Cirrhotic patients with HBV reactivation had a significantly higher proportion of developing hepatic failure (45.0% vs 20.3%, P<0.001), acute-on-chronic liver failure (ACLF) (31.4% vs 21.8%, P=0.005), and short-term death (14.0% vs 5.9% for 28-day, and 23.3% vs 12.4% for 90-day, both P<0.001) than those without. HBV reactivation is an independent risk factor of 90-day mortality for cirrhosis patients (OR=1.70, P=0.005), as well as hepatic encephalopathy, ascites and bacterial infection. Conclusion: This study clearly demonstrated that there was a high prevalence of HBV reactivation in CHB patients, which was mainly triggered by discontinued antiviral treatment. The HBV reactivation strongly increased the risk of developing hepatic failure, ACLF and short-term death in HBV-related cirrhotic patients, which may suggest that HBV reactivation would be a new challenge in achieving the WHO target of 65% reduction in mortality from hepatitis B by 2030.